2021
DOI: 10.3390/ijms22137122
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lipopolysaccharide-Induced Inflammatory Challenge on β-Glucuronidase Activity and the Concentration of Quercetin and Its Metabolites in the Choroid Plexus, Blood Plasma and Cerebrospinal Fluid

Abstract: Quercetin-3-glucuronide (Q3GA), the main phase II metabolite of quercetin (Q) in human plasma, is considered to be a more stable form of Q for transport with the bloodstream to tissues, where it can be potentially deconjugated by β-glucuronidase (β-Gluc) to Q aglycone, which easily enters the brain. This study evaluates the effect of lipopolysaccharide (LPS)-induced acute inflammation on β-Gluc gene expression in the choroid plexus (ChP) and its activity in blood plasma, ChP and cerebrospinal fluid (CSF), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…12,13 In vitro and animal studies on rodents showed the potential of phenolic and methylxanthine compounds to penetrate the brain and potentially exert neuroprotective benefits. [13][14][15][16] However, cell and animal studies present some limitations as many of the available in vitro studies do not take into consideration the use of physiological and dietary-achievable doses in their design, and the comparability of animal models with human physiology in terms of metabolic transformations tends to be lacking in animal studies. 17 In addition, little is known about the preferable route used (simple diffusion or carrier-mediated transport) and the brain bioavailability of ( poly)phenols and methylxanthines.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 In vitro and animal studies on rodents showed the potential of phenolic and methylxanthine compounds to penetrate the brain and potentially exert neuroprotective benefits. [13][14][15][16] However, cell and animal studies present some limitations as many of the available in vitro studies do not take into consideration the use of physiological and dietary-achievable doses in their design, and the comparability of animal models with human physiology in terms of metabolic transformations tends to be lacking in animal studies. 17 In addition, little is known about the preferable route used (simple diffusion or carrier-mediated transport) and the brain bioavailability of ( poly)phenols and methylxanthines.…”
Section: Introductionmentioning
confidence: 99%